Popular Banjar Song: Study on Music Form and Media Culture - Hadi, Sumasno; Sulisno, Sulisno (Harmonia: Journal of Arts Research and Education, 2021)
Technological developments in society and their social practices contribute to the popularity of folk songs. In this regard, this study aims: (1) to analyze the form of popular Banjar song music, and (2) to analyze the discourse and culture-media context that underpins the popularity of the Banjar song. This research was conducted using qualitative methods with data collection strategies including observation, document studies, questionnaires, and interviews. In the aspect of content, analysis of the form of music is carried out in stages: (1) notating the popular Banjar song document; (2) analyzing the form/structure of the music; (3) presenting the elements of the music form, and (3) making conclusions. Meanwhile, in studying the culture-media discourse on popular Banjar songs, it is carried out using the Pierre Bourdieu’s social practice approach which focuses on the concepts of habitus, capital, and the cultural field. Based on the analysis that has been carried out, it is known that popular Banjar songs have basic forms with three variations, namely the form of one part (A), two parts (AB), and three parts (ABC). However, it shows that most of the songs that exist are in the form of two parts, with a tendency to use major tonality. This finding confirms that the popular Banjar song is a product of mass culture, namely artworks produced from the popular culture ecosystem. In this study, it is also found that social and symbolic capital in the popularity of the Banjar song becomes a social practice that takes place in the cultural field of the people of South Kalimantan. The cultural field is a social space for cultural agents to actualize the popularity of the Banjar song.